DEVELOPING FAIRY TALE COMIC AS TEACHING MEDIA - Wahiddin, Hafizh Abdurrafi; Latif, Amirudin; Baihaqi, Yasmika (Journal of English Education and Enterpreneurship (JEEP), 2021)
This research aims to produce comic media product which is suitable for use by tenth grade students at second semester in English learning especially Narrative Text. This research used adaptation of development procedures by Sugiyono through seven stages of development. There are Potential and Problem, Data Collecting, Product Design, Design Validity, Design Improvements, Product Trial and Product Revision (revision 2). The research subject was the tenth grade students of SMA Muhammadiyah 1 Purbolinggo. Data collection was carried out by using a questionnaire and interview. The instrument of this research is in the form of validation sheet and assessment sheet. The researcher used the tabulation and calculating the average score as Data analysis techniques. The comic media which is developed has been feasible to be applied in learning after getting a good score in validation stage. The average scores of of the validation I of the material experts and media experts are 4.00 and 3.70 and the average scores of of the validation II of the material experts and media experts are 4,13 and 3,93 respectively. In addition, assessments that was given to students at the product trial stage obtained good score with an average score 4,02. In conclusion, the Fairy Tale comic is a comic media in teaching English especially Narrative Text. It is developed by using the adaptation of development procedures by Sugiyono. The Fairy Tale Comic can fulfill the objectives of the research and attract students' interest and motivation in learning English. It is suggested that the next researchers develop the comic media for other materials of Englsih and have more than one school as the subject of research in assessing the comic so the revision can be gained from different perspective of students.